Comparative evaluation of four systems for determining susceptibility of gram-positive organisms. - Henry, D (1986)
A study was undertaken to compare four commercial systems for testing the antimicrobial susceptibility patterns of gram-positive cocci. The reference method was an agar dilution method. The systems evaluated were the MS-2 system (Abbott Diagnostics Div., Mississauga, Ontario), the AutoMicrobic system (AMS) (Vitek Systems, Inc., Hazelwood, Mo.) with the gram-positive susceptibility (GPS) card, the Sceptor system (BBL Microbiology Systems, distributed by Becton Dickenson, Canada Inc., Mississauga, Ontario), and the Micro-Media system (Beckman Instruments, Inc., Anaheim, Calif.). There was a greater than 98% essential accord (EA) between all test results and the reference method results when testing 134 isolates of Staphylococcus aureus. In testing 79 isolates of coagulase-negative staphylococci the EA was greater than 97% with all systems except the MS-2. In the MS-2 system only, 30% of tests were interrupted by the instrument because of insufficient growth in the control chamber. Excluding the Sceptor system, the EA was greater than 96% on testing 70 isolates of enterococcus. In testing 15 isolates of group B Streptococcus there was 91% EA with the AMS and Sceptor systems and only 71 and 88% EA with the MS-2 and Micro-Media systems, respectively. The new AMS GPS MIC card was tested against 29 methicillin-resistant S. aureus, 10 coagulase-negative staphylococci, and 9 enterococci, and it gave more accurate results than the earlier GPS breakpoint card. The Micro-Media and MS-2 systems did not reliably detect marginally methicillin-resistant S. aureus. The MS-2 was the least expensive system to operate on a cost per test basis ($3.59 Can.), whereas the Sceptor was the most expensive system ($5.29 Can.). The AMS ws the least labor intensive (0.9 min per test), and the Sceptor system was the most time consuming (2.9 min per test).